Passive and active adaptive management: Approaches and an example - Williams, Byron (Journal of Environmental Management, 2010)
Adaptive management is a framework for resource conservation that promotes iterative learning-based decision making. Yet there remains considerable confusion about what adaptive management entails, and how to actually make resource decisions adaptively. A key but somewhat ambiguous distinction in adaptive management is between active and passive forms of adaptive decision making. The objective of this paper is to illustrate some approaches to active and passive adaptive management with a simple example involving the drawdown of water impoundments on a wildlife refuge. The approaches are illustrated for the drawdown example, and contrasted in terms of objectives, costs, and potential learning rates. Some key challenges to the actual practice of AM are discussed, and tradeoffs between implementation costs and long-term benefits are highlighted.

The role of social learning in adaptiveness: insights from water management - Lebel, Louis; Grothmann, Torsten; Siebenhüner, Bernd (International Environmental Agreements: Politics, Law and Economics, 2010)
The article introduces the notion of adaptiveness and discusses the role of social learning in it. Adaptiveness refers to the capacity of a social actor or social–ecological system to adapt in response to, or in anticipation of, changes in the environment. We explore arguments both from a theoretical perspective and through illustrations from case studies of water management in the Alps of Europe and Mekong in southeast Asia. We propose and illustrate that social learning processes are important for building adaptiveness in several ways and at different scales. Social learning can help cope with informational uncertainty; reduce normative uncertainty; build consensus on criteria for monitoring and evaluation; empower stakeholders to take adaptive actions; reduce conflicts and identify synergies between adaptations; and improve fairness of decisions and actions. Findings in the case studies provide some support for these generalizations but often with caveats related to diversity of stakeholder interests, levels of shared understanding versus contested knowledge and scale of coordination. For this reason, we suggest that future work pays greater attention to issues of agency, knowledge and scale: What strategies have individuals and organizations pursued in successful examples of social learning? How are the boundaries and interactions between science, policy and practice managed? How does social learning occur across spatial and temporal scales?
Keywords: Adaptation; European Alps; Fairness; Mekong River; Social learning; Uncertainty; Water management

Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, surfacing in everything from mundane agency permits to grand presidential proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it working? Does appending “adaptive” in front of “management” somehow make natural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their evaluations, however, have rested on theory, program-specific surveys, and isolated case studies. This article provides the first comprehensive review of adaptive management from the perspective that likely matters most to the natural resource agencies practicing adaptive management - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end product in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and practice leads to profound disparities between how agencies justify decisions and how adaptive management in practice arrives at the courthouse doorsteps. In Part II we review how these disparities have played out in courts considering claims that agency practice of adaptive management has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends from the existing case law to draw lessons for agencies and Congress about the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and one that survives judicial scrutiny - but agencies must be more disciplined about its design and implementation. This includes resisting the temptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeholder participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural resources policy to confront problems of the future as daunting as climate change.

Adaptive management of an environmental watering event to enhance native fish spawning and recruitment - King, A. J.; Ward, K. A.; O’connor, P.; Green, D.; Tonkin, Z.; Mahoney, J. (Freshwater Biology, 2010)
1. A common goal of many environmental flow regimes is to maintain and/or enhance the river’s native fish community by increasing the occurrence of successful spawning and recruitment events. However, our understanding of the flow requirements of the early life history of fish is often limited, and hence predicting their response to specific managed flow events is difficult. To overcome this uncertainty requires the use of adaptive management principles in the design, implementation, monitoring and adjustment of environmental flow regimes. 2. The Barmah-Millewa Forest, a large river red gum forest on the Murray River floodplain, south-east Australia, contains a wide variety of ephemeral and permanent aquatic habitats suitable for fish. Flow regulation of the Murray River has significantly altered the natural flood regime of the Forest. In an attempt to alleviate some of the effects of river regulation, the Forest’s water regime is highly managed using a variety of flow control structures and also receives targeted Environmental Water Allocations (EWA). In 2005, the largest environmental flow allocated to date in Australia was delivered at the Forest. 3. This study describes the adaptive management approach employed during the delivery of the 2005 EWA, which successfully achieved multiple ecological goals including enhanced native fish spawning and recruitment. Intensive monitoring of fish spawning and recruitment provided invaluable real-time and ongoing management input for optimising the delivery of environmental water to maximise ecological benefits at Barmah-Millewa Forest and other similar wetlands in the Murray-Darling Basin. 4. We discuss possible scenarios for the future application of environmental water and the need for environmental flow events and regimes to be conducted as rigorous, large-scale experiments within an adaptive management framework.
Keywords: floodplain river; regulated flows

Accountability and Learning: Exploding the Myth of Incompatibility between Accountability and Learning - Guijt, Irene (NGO Management, 2010)
When accountability is understood as reporting on pre-deined deliverables, it is often considered to be irreconcilable with learning. This conventional wisdom inhibits an appreciation of their connection. In this chapter, Irene Guijt exposes the laws and traps in reasoning that keep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountability and learning to complement each other.

Developmental Evaluation: Applying Complexity Concepts to Enhance Innovation and Use - Patton, Michael Quinn (Guilford Press, 2010)
Developmental evaluation (DE) offers a powerful approach to monitoring and supporting social innovations by working in partnership with program decision makers. In this book, eminent authority Michael Quinn Patton shows how to conduct evaluations within a DE framework. Patton draws on insights about complex dynamic systems, uncertainty, nonlinearity, and emergence. He illustrates how DE can be used for a range of purposes: ongoing program development, adapting effective principles of practice to local contexts, generating innovations and taking them to scale, and facilitating rapid response in crisis situations. Students and practicing evaluators will appreciate the book's extensive case examples and stories, cartoons, clear writing style, "closer look" sidebars, and summary tables. Provided is essential guidance for making evaluations useful, practical, and credible in support of social change.See also Developmental Evaluation Exemplars, edited by Michael Quinn Patton, Kate McKegg, and Nan Wehipeihana, which presents 12 in-depth case studies.
Keywords: Evaluation; Measurement; Organizational effectiveness; Project management

Quality standards for development evaluation - OECD; Development Assistance Committee (OECD, 2010)
Based on a broad international consultative process, the DAC Quality Standards for Development Evaluation are a reference guide to good practice in development evaluation. With a view to improving the quality of evaluation processes and products, and facilitating collaboration, this reference guide lays out standards for each phase of a typical evaluation process: from defining purpose, to planning, designing, implementing, reporting, and learning from and using evaluation results.
OCLC: 631212078

Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesize and interpret information in context, and transform or "fuse" disparate items of information into coherent knowledge. The chapters examine these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, doctors, inventors), across contexts (e.g. space and space analogs, corporate organizations, command and control, crisis and crowd management, air traffic control, the operating room, product development), and for both individual and team performance. Successful information integration is a key factor in the success of diverse endeavors, including team attempts to climb Mt. Everest, crowd control in the Middle East, and remote drilling operations. This volume is divided into four sections, each with a specific focus on an area of expert performance, resulting in a text that covers a wide range of useful information. These sections present well-researched discussions, such as: the management of complex situations in various fields and decision contexts; technological and training approaches to facilitate knowledge management by individual experts and expert teams; new or neglected perspectives in expert decision making; and the importance of ‘modeling’ expert performance through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapping such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners of Naturalistic Decision Making and those who study Expertise; Organizational and Cognitive Psychologists; and researchers and students in Business and Engineering.

The Clash of the Counter-bureaucracy and Development - Natsios, Andrew (The Center for Global Development, 2010)
In this essay, Andrew Natsios gives a first-hand account of what he finds most hinders USAID—layers of bureaucracy that misguide and derail development work.